2008
DOI: 10.1002/jso.21061
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intraperitoneal chemotherapy: Nomenclature and modalities of perfusion

Abstract: Following international consensus, HIPEC should be the acronym used in the scientific literature to refer to the hyperthermic intraperitoneal chemotherapy. Several modalities of perfusion are used to deliver HIPEC: open abdominal technique (Coliseum), closed abdominal technique, peritoneal cavity expander, semi-opened abdominal technique. There is no sufficient evidence in literature confirming the superiority of one technique over the others in terms of outcome, morbidity and safety to the personnel of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 28 publications
0
88
0
3
Order By: Relevance
“…Elias et al compared two groups of patients with colorectal carcinomatosis where one was treated with EPIC using 5FU and mitomycin C and the other with HIPEC using oxaliplatin 43°C. Morbidity, mortality, recurrence rate and overall survival favoured the HIPEC group [19,22].…”
Section: Early Postoperative Intraperitoneal Chemotherapymentioning
confidence: 93%
See 3 more Smart Citations
“…Elias et al compared two groups of patients with colorectal carcinomatosis where one was treated with EPIC using 5FU and mitomycin C and the other with HIPEC using oxaliplatin 43°C. Morbidity, mortality, recurrence rate and overall survival favoured the HIPEC group [19,22].…”
Section: Early Postoperative Intraperitoneal Chemotherapymentioning
confidence: 93%
“…Regardless of the rapid metabolism of the drug in the liver and at other sites in the body compartment, a large AUC ratio of peritoneal fluid to plasma was maintained. An increased risk of infection has been reported in patients who have received EPIC [19]. In a large multi-institutional retrospective study, EPIC was found to significantly increase the rate of postoperative complications in 504 patients with colorectal PC treated with CRS/IPC [21].…”
Section: Early Postoperative Intraperitoneal Chemotherapymentioning
confidence: 97%
See 2 more Smart Citations
“…Hospitals have designated rooms for mixing and preparation of chemotherapy/cytotoxic drugs to minimize the exposure to the staff involved in administering the treatment. In HIPEC a heated chemotherapy solution (1-2 l) is circulated in the peritoneal cavity for 30-90 min using a roller pump and circuit [40,41]. During this procedure the abdomen is either kept closed (Closed technique) or open (coliseum or open technique) [42,43].…”
Section: Perioperative Chemotherapymentioning
confidence: 99%